2006
DOI: 10.1007/s11199-006-8876-7
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Beliefs About the Influence of Ability and Effort in Sport and Physical Activity

Abstract: The purpose of this study was to explore gender differences in reasoning about the relationships between natural ability, effort/practice, and final skill level/performance across 16 physical activities at both elite and recreational levels. The participants were 153 college students enrolled in 6 physical activity classes. They completed 2 questionnaires. The results indicated that in physical activity domains, male students tended to rate natural ability as more influential for successful skill level or perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 46 publications
(68 reference statements)
0
11
1
2
Order By: Relevance
“…entity theory) than girls. This result was confirmed by the study of Li et al (2006), in which natural ability was rated as more influential for successful skill level or performance by boys than by girls, but differences for gender-linked activities were found. Finally, girls were less likely to adopt an incremental theory of athletic ability than boys (Li et al, 2004) and the review of Vella et al (2016) showed that participant gender moderated the relationship between incremental beliefs and adaptive outcomes.…”
Section: The Effects Of Demographic Variablesmentioning
confidence: 55%
“…entity theory) than girls. This result was confirmed by the study of Li et al (2006), in which natural ability was rated as more influential for successful skill level or performance by boys than by girls, but differences for gender-linked activities were found. Finally, girls were less likely to adopt an incremental theory of athletic ability than boys (Li et al, 2004) and the review of Vella et al (2016) showed that participant gender moderated the relationship between incremental beliefs and adaptive outcomes.…”
Section: The Effects Of Demographic Variablesmentioning
confidence: 55%
“…Scraton 1992;Wright 1997Wright , 1999, as well as positivist research (e.g. Lightbody et al 1996;Klomsten, Marsh, and Skaalvik 2005;Li, Lee, and Solmon 2006), addressing access and equity, hegemony, resistance, and the body. Much of the early work on gender and performance in physical education was informed by a liberal feminist perspective that argued for the inclusion of the binary 'girls' in a spectrum of physical activities and sports that were considered the preserve of 'boys'.…”
Section: Gender and Ability In Pementioning
confidence: 99%
“…In educational settings, males are more likely than females to attribute success to stable factors, for instance in ability, while females are more likely than males to attribute success to unstable factors like effort 16–18 . In the area of physical activity, Li et al 19 explored gender differences in how college‐aged individuals reasoned about natural ability, practice effort during physical activity, and final skill performance. Overall, males appraised natural ability as more influential in successful skill performance than females; however, there is some partial evidence supporting that perceptions about the influence of ability varied for activities that were perceived to be traditionally performed by a particular gender (ie, gender‐linked).…”
mentioning
confidence: 99%